Using the perceptually oriented approach to optimize spatial presence & ego-motion simulation - Riecke, B.E.; Schulte-Pelkum, J. (MPI for Biological Cybernetics, 2006)
This chapter is concerned with the perception and simulation of ego-motion in virtual environments, and how spatial presence and other higher cognitive and top-down factors can contribute to improve the illusion of ego-motion in virtual reality (VR). In the real world, we are used to being able to move around freely and interact with our environment in a natural and effortless manner. Current VR technology does, however, not yet allow for natural, real-life-like interaction between the user and the virtual environment. One crucial shortcoming in current VR is the insufficient and often unconvincing simulation of ego-motion, which frequently causes disorientation, unease, and motion sickness. We posit that a realistic perception of ego-motion in VR is a fundamental constituent for spatial presence and vice versa. Thus, by improving both spatial presence and ego-motion perception in VR, we aim to eventually enable performance levels in VR similar to the real world for basic tasks, e.g., spatial orientation and distance perception, which are currently very problematic cases. Users frequently get lost easily in VR while navigating, and simulated distances appear to be compressed and underestimated compared to the real world (Witmer & Sadowski, 1998; Chance, Gaunet, Beall, & Loomis, 1998; Creem-Regehr, Willemsen, Gooch, and Thompson, 2003; Knapp, 1999; Thompson, Willemsen, Gooch, Creem-Regehr, Loomis, & Beall, 2004, Stanney, 2002).
Keywords: MPI-TR; Riecke; Riecke_2006; TR; bernhard-riecke; iSpaceWeb; vection